Communicative Functions of Code Glosses in Academic Discourse - Hüseyin Kafes (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
A considerable amount of research has already established that academic writing is an interactive accomplishment, the success of which largely depends on appropriate writer-reader relationship. Yet, the nature of this relationship has been the subject of few studies. Also scarce are the studies on how academic writers address the needs of their readers and so, through elaboration, manage their interactions with them. Drawing on a corpus of 68 research articles (RAs) from the field of applied linguistics, this study explores how experienced writers (EWs) and novice writers (NWs) elaborate their ideas in their RAs to address their readers’ needs, and in so doing, manage their relations with them. Analysis of the corpus revealed that reformulation and exemplification, complex features of academic writing, serve important rhetorical functions. The results also show that these two groups of writers manage writer-reader relationship differently, differing in the type, number, (un)even distribution, and use of code glosses. These results are discussed, and pedagogical implications are offered.